How does the adjustment of training task difficulty level influence tactical behavior in soccer? - Machado, J.; Barreira, D.; Teoldo, I.; Travassos, B.; Júnior, J.; Santos, J.; Scaglia, A. (Research Quarterly for Exercise and Sport, 2019)
Purpose: This study aimed to investigate if player tactical skill level and age category influence team performance and player exploratory behavior in tasks with different difficulty levels. Method: In total, 48 youth male soccer players participated in the study (U15, n = 24, mean age = 13.06 ± 1.53 years; U17, n = 24, mean age = 16.89 ± 0.11 years). Player tactical skills were evaluated through the System of Tactical Assessment in Soccer (FUT-SAT), allowing them to be organized into three groups according to tactical efficiency: Higher tactical skill level (Group 01), Intermediate tactical skill level (Group 02), and Lower tactical skill level (Group 03). Next, Group 01 and Group 03 of both categories performed six Small-Sided and Conditioned Games (SSCG) each, namely three High difficulty SSCGs and three Low difficulty SSCGs. Team performance and players' exploratory behavior were analyzed through the Offensive Sequences Characterization System and Lag Sequential Analysis, respectively. Results: We found that team performance and players' exploratory behavior were influenced both by the age and tactical skill level of the players, as well as by task difficulty level. Conclusion: Therefore, in an attempt to improve player performance, practitioners must carefully manipulate key task constraints to adapt training task difficulty levels to player age and tactical skill level.